Ethical issues in unprofessional behavior of residents who dispute dismissal: ten year analysis of case law in hospital-based specialties - Judith Godschalx-Dekker; Sebastiaan Pronk; Gert Olthuis; Rankie ten Hoopen; Walther van Mook (BMC Medical Ethics)
Abstract Background Residents who do not internalize professional values may not be a good fit for their specialty and compromise the quality of their patient care. Research aimed at recognizing residents’ shortcomings in professionalism may help to prevent future shortcomings towards patients. The aim of this study was to increase insight into residents’ shortcomings in medical professionalism in light of professional values relevant within residency training. Methods We analyzed all law cases from the Dutch national conciliation board from 2011 to 2020 on the unprofessional behaviors described. Results During the period investigated, 61 dismissed residents challenged their dismissal. In 39 of 61 cases (64%), the program director named unprofessional behavior(s) as (one of the) reasons for dismissal. The most prevalent deficit of residents deemed unprofessional was poor self-awareness (80%); less prevalent deficits were: shortness of engagement and dishonest and disrespectful behavior (31% or less). Conclusions We describe perceived unprofessional behavior in residency, which was not about exceptional or abominable behaviors. For the most part, these behaviors concerned the accumulation of remediation-resistant day-to-day underperformance, discrediting trust and professional reliability. This finding encourages dedicated longitudinal assessment of professionalism and fuels the ethical debate about required professional values in hospital care.